Accessibility to public spaces: Boosting ecosystem services in urban areas in four Latin American cities - Montoya-Tangarife, Claudia; Villamizar Duarte, Natalia; Jorquera Guajardo, Felipe; Cardenas, María F.; Giraldo-Ospina, Tania (Frontiers in Sustainable Cities, 2022)
The supply and demand of ecosystem services in urban areas depends, among other things, on the configuration and location of public spaces with vegetation and the access citizens have to them. Providing equitable access to urban services has been a top priority of public policy worldwide, but urban ecosystem services (UES) are not always considered when discussing urban services. Since access to UES may positively impact wellbeing and promote urban sustainability, we analyze accessibility to public spaces with different greening characteristics in four Latin American cities: Cartagena de Indias and Medellín (Colombia) Valparaíso (Chile) and Quito (Ecuador). We argue that considering distribution of, and accessibility to, public spaces with different greening characteristics provides insights for policymakers seeking to increase the potential provision of UES through public space. We classified existing public spaces into four categories using photointerpretation of high-resolution QuickBird satellite images: (1) tree predominance, (2) grass predominance, (3) hard zone predominance, and (4) bare soil predominance. We evaluated physical accessibility using spatial analysis of road networks, considering a walking distance that can be covered in different ranges of time. Our results show that three of the four cities have good accessibility to public spaces within 15 min. However, this distance increases when we focus on access to public spaces with vegetation and green areas (categories 1 and 2). This study contributes to research on ecosystem services by analyzing conditions of accessibility to public spaces which offer direct contact with nature and a potential supply of UES within urban areas. It also highlights the importance of conceiving and planning public space as direct providers of UES, an important aspect of improving environmental quality and positively impacting people's health and wellbeing.